2012
DOI: 10.1111/j.1439-0434.2012.01916.x
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Fungal and Bacterial Diseases of Cucumber Plants by Using the Spent Mushroom Substrate of Lyophyllum decastes and Pleurotus eryngii

Abstract: The protective effect of autoclaved water extract from spent mushroom substrate (AWESMS) and autoclaved spent mushroom substrate (ASMS) of the edible mushrooms Lyophyllum decastes (hatakeshimeji) and Pleurotus eryngii (eringi) against fungal and bacterial diseases was investigated on cucumber plants. When the plants were treated with AWESMS by spraying the first true leaves and inoculated with the target pathogen 7 days later, AWESMS of hatakeshimeji significantly reduced powdery mildew by Podosphaera xanthii,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 12 publications
0
20
0
1
Order By: Relevance
“…5) Arase et al (2013) reported that spraying a water extract of the SMS of Lyophyllum decastes (hatakeshimeji) suppressed the development of lesions caused by infection with rice blast fungus 6) (Pyricularia oryzae; syn: Magnaporthe oryzae 7) ). Similarly, Parada et al (2012) found that the treating cucumber seedlings with SMSs of Ly. decastes and Pl.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…5) Arase et al (2013) reported that spraying a water extract of the SMS of Lyophyllum decastes (hatakeshimeji) suppressed the development of lesions caused by infection with rice blast fungus 6) (Pyricularia oryzae; syn: Magnaporthe oryzae 7) ). Similarly, Parada et al (2012) found that the treating cucumber seedlings with SMSs of Ly. decastes and Pl.…”
Section: Introductionmentioning
confidence: 89%
“…edodes and H. marmoreus induced resistance to Alternaria sooty spot caused by Alternaria brassicicola in cabbage. 9) These protective effects of SMS treatment were attributed to the induction of systemic acquired resistance (SAR) 8) because of the lack of antifungal activity in the extracts. Indeed, the resistance of pepper (Capsicum annuum) against Phytophthora blight disease has been induced by treatment with a water extract of the SMS of Le.…”
Section: Introductionmentioning
confidence: 99%
“…lachrymans but not Corynespora leaf spot caused by Corynespora cassiicola or scab caused by Cladosporium cucumerinum. 7) The water extracts of SMS did not exhibit antimicrobial activity against the above fungal and bacterial pathogens. Therefore, the authors suggested that the protective effects of SMS were attributable to the induction of systemic acquired resistance (SAR) by SMS treatment.…”
Section: Introductionmentioning
confidence: 90%
“…6) Parada et al (2012) investigated the effect of SMS treatment on fungal and bacterial diseases of cucumber plants. 7) They sprayed water extracts of the SMSs of Ly. decastes and Pl.…”
Section: Introductionmentioning
confidence: 99%
“…Then, 500 g of fresh residual substrate were mixed with 1.5 L of distilled water and autoclaved (30 min, 120 °C). After cooling, the product was filtered and an aqueous extract of substrate (ESPO) was made (Parada et al 2012).…”
Section: Crude Extractsmentioning
confidence: 99%